Cellular Immune Response Evaluation in Nepalese Patients with Cutaneous Leishmaniasis - Shrestha, Srijan; Prajapati, Sabita; Shakya, Jivan; Aganja, Ram Prasad; Manandhar, Binod; Telford, William G.; Wallace, Paul K.; Gautam Ghimire, Pragya; Bastola, Anup; Chalise, Bimal Sharma; Manandhar, Krishna Das (Journal of Nepal Biotechnology Association, 2026)
Cutaneous leishmaniasis (CL) remains a clinically and immunologically heterogeneous disease influenced by parasite species and host immune responses. In this study, seventeen CL cases were assessed through lesion characteristics, histopathological analysis and Kinetoplast DNA (kDNA) nested Polymerase Chain Reaction (PCR)figure. Lesions mainly appeared on exposed body parts, especially the face (64.70%) and most patients had a single lesion. kDNA PCR confirmed CL in 58.82% (n=10) of cases, identifying Leishmania donovani (720 bp) in 5 cases and L. major (560–590 bp) 5 cases as the circulating species. Immunological analysis showed reduction in T-lymphocytes  in CL patients compared to Healthy Controls (HC), largely due to a significant decrease in CD8⁺ T cells (p=0.036), while CD4⁺ T cell levels remained stable. Further stratification based on CL PCR positivity showed that reductions in T-lymphocytes (p=0.045) were confined to patients with confirmed Leishmania infection, again attributed mainly to decreased CD8⁺ T cells (p=0.040). No notable changes were observed in B cells, NK cells, or NKT cells. These findings highlight CL infection positivity status-dependent variations in host immune responses and emphasize the importance of CD8⁺ T-lymphocytes in CL pathogenesis and disease outcome.